ナンキョク ニオケル チュウソウ タイキ ノ ソウゴウ カンソク f. キョクイキ デンリソウ ダイ2カイ キョクイキ ニオケル デンリケン ジキケン ソウゴウ カンソク シンポジウム PART 2 - 福西, 浩; フクニシ, ヒロシ; 川口, 貞男; カワグチ, サダオ; FUKUNISHI, Hiroshi; KAWAGUCHI, Sadao (1980)
P(論文) 地上10-120kmの成層圏から電離圏に至る大気領域の構造を明らかにするために,1982年から4年間MAP(中層大気国際協同観測計画)が実施されようとしている.南極昭和基地でもこの計画の一環として,地上観測網,航空機,気球,ロケット,衛星を用いた中層大気の総合的な計画が立案されつつある.ここではこの計画の概要を示す. The Inter-Union Special Committee on Solar-Terrestrial Physics (SCOSTEP) has proposed to carry out the Middle Atmosphere Program (MAP) in 1982-1985 as an international scientific project. Coordinated observations of the middle atmosphere in the area around Syowa Station in Antarctica by means of ground-based station network, aircraft, balloons, rockets and satellites are now under consideration in order to study structures and seasonal and diurnal variations of the polar middle atmosphere in the altitude range of 10-120 km. The report gives an outline of this project. departmental bulletin paper